Flagellar hook flexibility is essential for bundle formation in swimming Escherichia coli cells. - Brown, M; Steel, B; Silvestrin, C; Wilkinson, D; Delalez, N; Lumb, C; Obara, B; Armitage, J; Berry, R (2012)
Swimming Escherichia coli cells are propelled by the rotary motion of their flagellar filaments. In the normal swimming pattern, filaments positioned randomly over the cell form a bundle at the posterior pole. It has long been assumed that the hook functions as a universal joint, transmitting rotation on the motor axis through up to ∼90° to the filament in the bundle. Structural models of the hook have revealed how its flexibility is expected to arise from dynamic changes in the distance between monomers in the helical lattice. In particular, each of the 11 protofilaments that comprise the hook is predicted to cycle between short and long forms, corresponding to the inside and outside of the curved hook, once each revolution of the motor when the hook is acting as a universal joint. To test this, we genetically modified the hook so that it could be stiffened by binding streptavidin to biotinylated monomers, impeding their motion relative to each other. We found that impeding the action of the universal joint resulted in atypical swimming behavior as a consequence of disrupted bundle formation, in agreement with the universal joint model.